Internet addiction in adolescents (literature review) - Potupchik, Tatiana V.; Mantikova, Anna V.; Lapteva, Lyudmila V.; Chudinova, Olga V. (The New Research of Tuva, 2024)
The article provides a systematic review and analysis of literature on the main aspects of internet-dependent behavior among adolescents. It considers both Russian and foreign publications, including research on the prevalence of internet addiction (IA) from 2010 to 2023 and its impact on somatic and neuropsychiatric health. Special attention is given to the epidemiological, clinical, functional, and neurobiological aspects of internet-dependent behavior among adolescents, as well as the impact of this disorder and its specific manifestations (such as dependence on computer games, social media, and smartphones) on the physical and mental health of internet users.A significant increase in unregulated internet use among adolescents and young people in many countries has been noted, especially during the COVID-19 pandemic. This has led to an emphasis on the importance of internet use among these populations as a significant medical, social, psychological, and pedagogical issue.Significant variability in the prevalence of IA has been observed across different countries and regions, as well as its relationship with the age, gender, and ethnicity of those surveyed. Most studies have focused on the general IA, without distinguishing between specific forms. This highlights the need for a more detailed understanding of IA's structure and the impact of its components on young internet users' health. The lack of studies on the prevalence of IA among adolescents and young people in urban and rural areas, as well as insufficient attention to its ethnic aspects and the extremely limited number of studies on IA in the national republics of the Russian Federation, were noted.The relative lack and fragmented nature of research on identifying risk factors, determining the informational significance and contribution of a wide range of indicators (biomedical, clinical-functional, metabolic, and psychosocial), as highly probable predictors of internet-dependent behavior, is emphasized. It is concluded that there is a need to develop unified methodological approaches to studying the epidemiological aspects of this condition, and the importance of using internationally recognized informative test questionnaires is highlighted.
Keywords: adolescence; Internet; online behavior; addiction; review